Leadership identity: an interpretive phenomenological analysis of how undergraduate fraternity New Member Educators understand and experience leadership - Lopez, Keith, author; Kuk, Linda, advisor; Anderson, Sharon, committee member; Bimper, Albert, committee member; Whipple, Ed, committee member (Colorado State University. Libraries, 2021)
The purpose of this study was to focus on how New Member Educators understand and experience their role as a leader within their organization as well as how they perceive their role in leading their organization into the future. Overall, the overarching question of this study is the following: What is the experience of undergraduate fraternity New Member Educators concerning their leadership identity in relation to their organization? Additionally, research questions focused on how these men experience and identify themselves as leaders, how they understand their leadership as it relates to their organization, how they experience their leadership influencing the congruence of the behavior with the stated values of their organization and finally, how they perceive their role in leading their organizations into the future. To examine the development of leadership identity for undergraduate fraternity New Member Educators and their understanding of the way their role and experiences relate to their organization, this research study utilized an interpretative phenomenological analysis (IPA) (Smith, Flowers, & Larkin, 2009). Through choosing IPA, the researcher made a commitment to explore and interpret the way participants made meaning of their own experiences through gaining access to detailed personal accounts (Smith et al., 2009) of nine New Member Educators concerning their leadership identity in relation to their organization. The analysis detailed several themes in which the participants provided a broad range of perspectives on their experience concerning their leadership identity related to their organization, Delta Delta Alpha. There were four superordinate themes that emerged from the analysis. These included: being able to comprehend leadership, being conferred to lead, being compelled to lead, and understanding and experiencing congruent leadership. Within each superordinate theme, two to three ordinate themes were identified. The themes identified and derived through the interpretive phenomenological analysis of the data lead to the development of the essence of the experience of undergraduate fraternity New Member Educators. This essence of the experience of these men concerning their leadership identity in relation to their organization subsequently created the findings within this study. The findings within this study led to the identification of five components that could be considered for use in future research, investigation, action and practice. This study focused on one organization (Delta Delta Alpha) and one position within the organization (New Member Educator). Thus, these five components could be explored further in terms of how fraternity men (and perhaps, more specifically New Member Educators) consider their leadership identity in relation to their organization. These five components were: modeling, reflection, experience, motivation and congruence. These components could potentially be used within leadership practice in terms of how men in fraternal organizations consider their leadership identity.
Keywords: fraternity; IPA; New Member Educator; interpretive phenomenological analysis; college student leadership; leadership identity